The use of a laser light-scattering technique in fluvial sediment measurement - Sulaiman, Mohd Yusof; Abd. Moksin, Mohd Maarof; Ibrahim, Shaharin; Leong, See King (Universiti Pertanian Malaysia, 1982)
In this paper, we report the measurement of sediment concentration using a laser light-scattering technique. In its present form, the technique suffers from several practical limitations but these are outweighed by the simplicity and speed of the technique. The procedures used in overcoming the accompanying problems are discussed.